2003
DOI: 10.1159/000072960
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines, Pleuropneumonia Infection and the Effect of Dexamethasone

Abstract: Objectives:Actinobacillus pleuropneumoniae causes an often fatal infection of swine due to pleuropneumonia. To determine if inflammatory cytokines are associated with A. pleuropneumoniae-induced pneumonia, infected and noninfected animals were concomitantly administered saline or dexamethasone. Methods: Twenty-four swine were treated with saline, A. pleuropneumoniae, dexamethasone, or A. pleuropneumoniae and dexamethasone (n = 6). The plasma levels of TNF-α, IL-1β, IL-6, IL-8, and IL-10 were examined through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(53 reference statements)
2
5
1
Order By: Relevance
“…of A. pleuropneumoniae. These results are inconsistent with some previous reports, in which no systemic changes in TNF-α and IL-1β could be detected in A. pleuropneumoniaeinfected pigs (Fossum et al, 1998;Balaji et al, 2002;Myers et al, 2004). Yet, Huang et al (1999) described an increase in TNF-α as well as IL-1β after both an in vitro and in vivo stimulation and infection with A. pleuropneumoniae, respectively.…”
Section: Contents Lists Available At Sciencedirectcontrasting
confidence: 99%
See 4 more Smart Citations
“…of A. pleuropneumoniae. These results are inconsistent with some previous reports, in which no systemic changes in TNF-α and IL-1β could be detected in A. pleuropneumoniaeinfected pigs (Fossum et al, 1998;Balaji et al, 2002;Myers et al, 2004). Yet, Huang et al (1999) described an increase in TNF-α as well as IL-1β after both an in vitro and in vivo stimulation and infection with A. pleuropneumoniae, respectively.…”
Section: Contents Lists Available At Sciencedirectcontrasting
confidence: 99%
“…In the current study, 80% of the pigs showed a marked IL-6 response following experimental infection with A. pleuropneumoniae and a maximal mean IL-6 concentration was recorded 10 h p.i. These findings are largely in agreement with other reports (Fossum et al, 1998;Lauritzen et al, 2003;Myers et al, 2004), including a very recent one from Tambuyzer et al (2014).…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 93%
See 3 more Smart Citations